A Microarray Dataset of Genes Expressed by the R28 Retinal Precursor Cell Line. (14th February 2013) - Seigel, Gail M.; Salvi, Richard J.
Abstract : The R28 rat retinal progenitor cell line was developed from postnatal day six rat retina immortalized with the 12S E1A gene of adenovirus. R28 cells have been distributed to over 100 laboratories worldwide, with over 60 publications on topics that include in vitro toxicology, cellular physiology, gene expression analysis, and experimental transplantation. In this paper, we present a microarray dataset of R28 cells that describes the presence or absence of 8799 genes and ESTs that may be relevant to current and future studies of R28 retinal precursor cells.